Brazil Current volume transport variability during 2009-2015 from a longterm moored array at 34.5°S - Chidichimo, María Paz; Piola, Alberto Ricardo; Meinen, Christopher S.; Perez, Renellys; Campos, Edmo; Dong, Shenfu; Lumpkin, Rick; Garzoli, S. L. (Journal of Geophysical Research: Oceans)
The Brazil Current, the western limb of the subtropical gyre of the South Atlantic Ocean, is one of the major Western Boundary Currents of the global ocean. Here, we present the first multiyear continuous daily time series of Brazil Current absolute volume transport obtained using 6+ years of observations from a line of four pressure-recording inverted echo sounders (PIES) deployed at 34.5°S. The array was augmented in December 2012 with two current meter-equipped PIES and in December 2013 with a moored Acoustic Doppler Current Profiler on the upper continental slope. The Brazil Current is bounded by the sea surface and the neutral density interface separating South Atlantic Central Water and Antarctic Intermediate Water, which is on average at a reference pressure of 628 ± 46 dbar, and it is confined west of 49.5°W. The Brazil Current has a mean strength of −14.0 ± 2.8 Sv (1 Sv ≡ 106 m3 s−1; negative indicates southward flow) with a temporal standard deviation of 8.8 Sv and peak-to-peak range from −41.7 to +20 Sv. About 80% of the absolute transport variance is concentrated at periods shorter than 150 days with a prominent peak at 100 days. The baroclinic component accounts for 85% of the absolute transport variance, but the barotropic variance is not negligible. The baroclinic and barotropic transports are uncorrelated, demonstrating the need to measure both transport components independently. Given the energetic high frequency transport variations, statistically significant seasonal to interannual variability and trends have yet to be detected. Fil: Chidichimo, María Paz. Ministerio de Defensa. Armada Argentina. Servicio de Hidrografía Naval. Departamento Oceanografía; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Instituto Franco-Argentino sobre Estudios del Clima y sus Impactos; Argentina. Centre National de la Recherche Scientifique. Institut de Recherche pour le Developpement. Département Ecologie, Biodiversité et Fonctionnement des Ecosystèmes Continentaux; Francia ...